Differential promotive voice–prohibitive voice relationships with employee performance: Power distance orientation as a moderator - Song, Jun (Springer Nature, 2020)
Increased attention has been paid to research on the outcomes of voice. However, the existing findings on the relationship between voice and employee performance are inconclusive. To address the insufficient understanding of the voice–employee performance relationship, this study proposed a model that specifies the relationships between two types of voice (i.e., promotive and prohibitive) and employee performance along with the moderating role of power distance orientation. The results of the analysis of a sample in China that comprised 80 leaders and 431 employees showed an inverted Ushaped relationship between promotive voice and employee performance and a positive linear relationship between prohibitive voice and employee performance. Power distance orientation was found to significantly moderate the nonlinear and linear relationships. Specifically, the inverted U-shaped relationship was more pronounced, while the positive linear relationship was weaker among employees with high power distance orientation. Theoretical and practical implications of the findings are discussed, along with the limitations of this study and future research directions.